Development Of Formulated Eurycoma Longifolia And Phyllanthus Niruri Extracts For Pharmacokinetic And Bioavailability Studies - Ma, Hai Qiu (2014)
The lignan-rich extract of Phyllanthus niruri (PNF5) normalises the plasma uric acid of hyperuricemic rats, and its effects are comparable to those of clinically used allopurinol. The quassinoid-rich extract of Eurycoma longifolia (TAF2) significantly improves the sperm count of male rats, and may be potentially suitable for managing male infertility. However, the oral bioavailability of the bioactive lignans, phyltetralin (PT) and phyllanthin (PL), in PNF5 and the quassinoids, 13α(21)-epoxyeurycomanone (EP) and eurycomanone (EN), in TAF2 were low due to the low aqueous solubility of the lignans and poor membrane permeability of the quassinoids. The present study led to the improvement of the oral bioavailabilities of PT and PL in PNF5, and EP and EN in TAF2 through incorporation in a Gelucire®44/14-based solid dispersion (SDC). In vitro studies, which were dissolution test and everted rat gut sac method indicated that PNF5-SDC formulation resulted in higher release of PT and PL, and TAF2-SDC resulted in higher permeation of EP and EN compared to the conventional powder-filled capsules (PFC) formulations. The pharmacokinetic parameters of PT, PL, EP and EN indicated that the rate of these compound movements from the central compartment to peripheral compartment were slow compared to the rate movement from the peripheral compartment to the central compartment (P < 0.001).